Peran Lembaga Keuangan Syariah Dalam Menerapkan Sistem Keuangan Inklusif Terhadap Pemberdayaan Masyarakat Kota Palopo - Riema Febriantie (JSE: Jurnal Sharia Economica, 2025)
This study aims to provide an understanding of the efforts made by Islamic Financial Institutions (LKS) in implementing financial inclusion, to identify the obstacles encountered, and to analyze the role of LKS in applying inclusive financial systems to empower communities in Palopo City. The research employed a survey method with a qualitative approach. The sources of information in this study were employees of Bank Syariah Indonesia (BSI) Palopo Branch and several micro-entrepreneurs. The results of the study indicate that various efforts have been made by LKS, and their implementation has been well received by the community in Palopo City. This is evidenced by several programs, products, and financing schemes provided to micro-entrepreneurs in the area. However, there are several obstacles faced, including limited human resources and service offices, as well as a lack of understanding and awareness among the public, who still prefer quick and simple loans. As a result, many people tend to carry out financial transactions outside the LKS system. Micro-entrepreneurs require the role of LKS, particularly in providing capital to expand their markets, thereby contributing significantly to the national economy. LKS are able to offer solutions to meet the basic needs of the community, both consumptive and productive, especially for the people of Palopo City.